Rincón L., E. de J. (1983). La libertad en "El Ser y la Nada" y la "Crítica de la razón dialéctica" de lean Paul Sartre. Trabajo de grado. Bogotá, Universidad Javeriana: Faculta de Filosofía. - Vergara Moreno, Franco Alirio; Pontificia Universidad Javeriana (2016)
null